Characterization of Green Betel Leaf Extract (Piper bettle L) as Raw Material for Mouthwash Preparations - Iwan Iskandar; Hevi Horiza; Mutia Yuhesti (Alliance oh Health Activists (AloHA), 2024)
Previous research reported that the phenol coefficient of a sample of betel leaf decoction disinfectant was only 0.3-0.5 ppm, because this compound evaporates easily with heat treatment. Therefore, in this research, a viscous extract from green betel leaves was carried out. Thus, it is necessary to characterize the condensed extract of green betel leaves from Kijang, Bintan Regency, Indonesia, which is used in the manufacture of mouthwash preparations. Based on the results of qualitative tests, the thick extract of green betel leaves contains tannins, saponins and flavonoids. Based on quantitative tests, it was found that the thick betel leaf extract contained 61.9032 ppm of antioxidants, 524.8148 ppm of flavonoids (0.53%), 219.44 ppm of tannins (0.22%), 3213.33 ppm of total phenols (3 .21%) and saponins 2542.22 ppm (2.54%) from 100 g sample. The content of these compounds can be used as part of herbal mouthwash formulas. Keywords: green betel leaf; extract; mouthwash